Recent updates on stabilization of recombinant enzymes via nanotechnology-based approaches - Shakeel Ahmed Ansari; Jakleen Abujamai; Asim Muhammad Alshanberi; Ruksana Satar (Discover Food)
Abstract The food and pharmaceutical industries dominate the global enzyme market, and the industrial demand for enzymes is continually rising. However, low yields, poor reproducibility, and occasionally subpar performance of these biocatalysts in their native form continue to restrict the use of enzymes. These limitations can be effectively addressed by recombinant DNA technology and protein engineering, which enables the high-volume production of newly redesigned enzymes with enhanced characteristics that satisfy industrial needs. Such recombinant enzymes find extensive application in food, dairy, bakery, brewing, wine and emulsifier/sweetener industries. Nanoparticles further advanced the use of these recombinant enzymes due to their distinct optical, chemical, physical and electrical characteristics. Nanotechnology based approaches promoted substantial immobilization yield as compared to planar 2-D surfaces due to their greater surface area to volume ratio. This technology offered stable catalytic activity of recombinant enzyme under a variety of operating conditions, sensitivity, response scale and reusability rates. This review highlights the state‐of‐the‐art properties of immobilization of industrially important recombinant enzymes.